1975
DOI: 10.1128/iai.12.6.1262-1270.1975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular construction of Clostridium botulinum type A toxins

Abstract: Two Clostridium botulinum type A toxic fractions, named large (L) and medium (M) toxins, were eluted from Sephadex G-200. Sucrose density gradient centrifugation resolved L toxin (2.5 x 10W to 3.0 x 108 mean lethal doses per mg of N) into two fractions, 19S and 16S. The same procedure performed at pH 8 resolved it into three fractions; the heavier two were both nontoxic and hemagglutinin positive, and the lightest one (7S) was toxic. M toxin (12S) (4.5 x 10W to 5.0 x 108 mean lethal doses per mg of N) was homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…of progenitor toxins HA-positive and HA-negative progenitor toxins were purified as described in section 2. As reported previously [2], the HA-positive progenitor toxin preparation is a mixture of 16S and 19S toxins and HA-negative progenitor toxin preparation is 12S toxin. These preparations were subjected to SDS-PAGE with a reducing agent ( Fig.…”
Section: Sds-pa Ge and N-terminal Amino Acid Sequence Analysessupporting
confidence: 61%
See 1 more Smart Citation
“…of progenitor toxins HA-positive and HA-negative progenitor toxins were purified as described in section 2. As reported previously [2], the HA-positive progenitor toxin preparation is a mixture of 16S and 19S toxins and HA-negative progenitor toxin preparation is 12S toxin. These preparations were subjected to SDS-PAGE with a reducing agent ( Fig.…”
Section: Sds-pa Ge and N-terminal Amino Acid Sequence Analysessupporting
confidence: 61%
“…The supernatant was precipitated with 60% saturated ammonium sulfate. After removing RNA in the precipitate by protamine treatment [2], this preparation was subjected to a SP-Toyopearl 650M (Tosoh, Tokyo, Japan) column equilibrated with 50 mM sodium acetate buffer (pH 4.2). The column was washed with 100 ml of this solution, and the concentration of NaC1 was then increased linearly to 0.5 M. The fractions which showed both toxic and hemagglutinating activity, and the fraction which showed only toxic activity were collected separately, concentrated by 70% saturation of ammonium sulfate, and then subjected to a Sephacryl S-300 (Pharmacia Biotechnology AB, Uppsala, Sweden) column equilibrated with 50 mM sodium acetate buffer (pH 4.2) containing 0.5 M NaC1, to obtain purified HA-positive (16S and 19S) and HA-negative (12S) progenitor toxins.…”
Section: Purification Of Progenitor Toxinsmentioning
confidence: 99%
“…Botulinum neurotoxin Α is produced by Clostridium botulinum as a protein complex composed of the 150 kDa core neurotoxin, various haemagglutinins and a protein known as the non-toxin non-haemagglutinin [39]. Three different complex species with molecular sizes of 900, 500 and 300 kDa, respectively, may be isolated from C. botulinum type A cultures [40]; however, in each case, the effect on their target cells is exerted by the free 150 kDa neurotoxin which is released after dissociation of these complexes [41]. Consequently, for the purposes of the present study, we used pure BoNT/A of 150 kDa instead of the commercial botulinum toxin formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Type B strains produce both 12 and 16s toxins in culture (Kozaki et al 1974). Schantz and Spero (1967) reported that type A strains produce 1 9 s toxin only in culture, whereas Sugii and Sakaguchi (1975) demonstrated that they produce only 12s toxin in culture. Lamanna and Sakaguchi (1971) proposed the term "progenitor toxin" to designate the toxin appearing first in culture and in food.…”
Section: Introductionmentioning
confidence: 99%